2022
DOI: 10.1039/d1mh01383a
|View full text |Cite
|
Sign up to set email alerts
|

Diindolocarbazole – achieving multiresonant thermally activated delayed fluorescence without the need for acceptor units

Abstract: We present a new multi-resonance thermally activated delayed fluorescence (MR-TADF) emitter paradigm, demonstrating that the structure need not require the presence of acceptor atoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
104
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 81 publications
(109 citation statements)
references
References 72 publications
(128 reference statements)
5
104
0
Order By: Relevance
“…30 The longest delayed component is attributed to pure monomer emission with mono-excitonic origin, in contrast with α-3BNOH where it was found to have bi-excitonic TTA contribution (Figure S13). As in other recent studies of MR-TADF materials, 15,18 we find that changing the host matrix has only a modest influence on kRISC (Figure S12b). Finally, the photoluminescence quantum yield (PLQY) of α-3BNMes in 1% mCP doped film was determined to be 63%, thus nearly double that of α-3BNOH (35% in 1 wt% mCP), and is sufficiently high to support OLED applications.…”
Section: Optical Propertiessupporting
confidence: 89%
See 1 more Smart Citation
“…30 The longest delayed component is attributed to pure monomer emission with mono-excitonic origin, in contrast with α-3BNOH where it was found to have bi-excitonic TTA contribution (Figure S13). As in other recent studies of MR-TADF materials, 15,18 we find that changing the host matrix has only a modest influence on kRISC (Figure S12b). Finally, the photoluminescence quantum yield (PLQY) of α-3BNMes in 1% mCP doped film was determined to be 63%, thus nearly double that of α-3BNOH (35% in 1 wt% mCP), and is sufficiently high to support OLED applications.…”
Section: Optical Propertiessupporting
confidence: 89%
“…14 MR-TADF compounds show TADF due to the alternating pattern of electron density between the ground and excited states that leads to small DEST, combined with upper-triplet crossings from thermally-populated Tn states back to the emissive S1 state. [15][16][17][18] The excited states thus possess a distinct short range charge transfer (SRCT) character, 13,19,20 and MR-TADF compounds are endowed with high singlet radiative decay (kr) rates of around 10 7 s -1 . 5,19 Despite these advantages, the RISC rates reported for MR-TADF materials typically lag ~100 times slower than those of leading D-A or D-A-D TADF materials.…”
Section: Introductionmentioning
confidence: 99%
“…[15] MR-TADF compounds show TADF due to the alternating pattern of electron density between the ground and excited states that leads to small ΔE ST , combined with upper-triplet crossings from thermally populated T n states back to the emissive S 1 state. [16][17][18][19] The excited states thus possess a distinct short-range charge transfer (SRCT) character, [14,20,21] and MR-TADF compounds are endowed with high singlet radiative decay (k r ) rates of around 10 7 s -1 . [5,20] Despite these advantages, the RISC rates reported for MR-TADF materials typically lag ~100 times slower than those of leading D-A or D-A-D TADF materials.…”
Section: Introductionmentioning
confidence: 99%
“…showed that the MR‐TADF emitters can exhibit both small Δ E ST and high fS1S0$f_{S_1 S_0}$, [ 42 ] which opens the possibility to increase the device performance. However, the MR‐TADF emitters are rare, and most of them are nanographenes doped with both donor and acceptor atoms, such as O, B, and N. [ 41 ] Recently proposed DilCzMes4 is the first acceptor‐free MR‐TADF that contains only nitrogen as donor, [ 43 ] showing an unexplored frontier in MR‐TADF design.…”
Section: Design Of Thermally‐activated Delayed Fluorescence Emittersmentioning
confidence: 99%